If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -4) = 6y Reorder the terms: 2(-4 + y) = 6y (-4 * 2 + y * 2) = 6y (-8 + 2y) = 6y Solving -8 + 2y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -8 + 2y + -6y = 6y + -6y Combine like terms: 2y + -6y = -4y -8 + -4y = 6y + -6y Combine like terms: 6y + -6y = 0 -8 + -4y = 0 Add '8' to each side of the equation. -8 + 8 + -4y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -4y = 0 + 8 -4y = 0 + 8 Combine like terms: 0 + 8 = 8 -4y = 8 Divide each side by '-4'. y = -2 Simplifying y = -2
| 38=86-2x | | 3d-1-4d=-7 | | (X-3)2=36 | | 6+2x=3x+3 | | 28=13+3x | | -5/18+23/18-17/18 | | 159x+x=29 | | 67=g-(-36) | | 5x.2x+1=61 | | 4x+6-2y-2= | | (4+3)x+2x-5= | | 9y-5y=28 | | 9y-5y= | | y=2-2/3x | | 2p+7/3=p-1/4 | | X^4+2X^3-2x^2-4X=0 | | 8x=18-10x | | 8x=150-7x | | 9x=55-2x | | 3x=49-4x | | -47+3x=9-10x | | 2n=-t^2+8 | | t^2=8-2n | | 2(5y+1)=8 | | 7x^(2/3)-62x^(1/3)-9=0 | | 5x=25+15 | | 25+15=5x | | 10-10x=64-24x | | 3(2x+3)+4(x+2)= | | 2x^(1/2)+x^(1/4)-6=0 | | 5(x-7)= | | 2x^(2/3)-15x^(1/3)-8=0 |